2022
DOI: 10.1186/s12889-022-13127-7
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and strategies to address COVID-19 testing hesitancy: a rapid scoping review

Abstract: Background Testing is a foundational component of any COVID-19 management strategy; however, emerging evidence suggests that barriers and hesitancy to COVID-19 testing may affect uptake or participation and often these are multiple and intersecting factors that may vary across population groups. To this end, Health Canada’s COVID-19 Testing and Screening Expert Advisory Panel commissioned this rapid review in January 2021 to explore the available evidence in this area. The aim of this rapid rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 46 publications
3
46
0
Order By: Relevance
“…Factors related to testing and vaccine hesitancy in our sample were generally consistent with findings from other studies. For example, a scoping review of testing hesitancy also identified consequences of testing among the common barriers to testing in five other studies, though concerns about reliability of tests were not reported ( 41 ). Similar to other qualitative studies of diverse populations [e.g., ( 42 44 )], numerous participants who expressed hesitation about the COVID-19 vaccine reported concerns about its safety and effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Factors related to testing and vaccine hesitancy in our sample were generally consistent with findings from other studies. For example, a scoping review of testing hesitancy also identified consequences of testing among the common barriers to testing in five other studies, though concerns about reliability of tests were not reported ( 41 ). Similar to other qualitative studies of diverse populations [e.g., ( 42 44 )], numerous participants who expressed hesitation about the COVID-19 vaccine reported concerns about its safety and effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Turnout in location 3 was higher (11.4%) than in locations 1 (1.7%) and 2 (1.3%), likely due to the longer pilot period and the higher number of test facilities. Although our study shows that testing uptake can be increased by facilitating access to testing, there are many other factors that influence testing motivation and testing uptake [ 30 , 31 ]. Studies in several other countries showed associations between educational level or ethnicity and low testing uptake [ 16 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate occupational inequalities that add to emerging evidence around sociodemographic inequalities in the implementation and uptake of mass testing programmes(35). Clear communication and support around testing at the employer and government level is likely to be crucial for future mass testing programmes, as unclear recommendations and fears around income loss or disruption to work may reduce workers’ engagement with testing(35,36). Workers’ personal usage of LFT devices was not investigated in this survey, but other behavioural surveys suggest low general population usage of LFTs in the UK (37).…”
Section: Discussionmentioning
confidence: 99%